Data for "Cryogenic ion trap system for high-fidelity near-field microwave-driven quantum logic" - Weber, M; Loschnauer, C; Wolf, J; Gely, M F; Hanley, R; Goodwin, J; Ballance, C; Harty, T; Lucas, D (University of Oxford, 2023)
Datasets used to generate the figures of "Cryogenic ion trap system for high-fidelity near-field microwave-driven quantum logic", accepted for publication in "Quantum Science and Technology"